The Effect of Owner-Manager’s Safety Leadership and Supervisor’s Safety Roles on Safety Performance in SME Manufacturing - Zulkifly, Syazwan Syah; Baharudin, Mohd Rafee; Mahadi, Muhammad Razif; Syed Ismail, Sharifah Norkhadijah (UUM Press, 2021)
Small and Medium Entrepreneurships (SME) is the backbone of the country economic growth. However, most of workplace accidents in Malaysia come from the SME sector. Considering financial and workforce limitations own by SMEs as compared to huge firms, this fact advocates the scholars and also practitioners of occupational safety and health (OSH) to find suitable and inexpensive approaches in improving safety performance of the SMEs. Based on previous researches, results showed that safety leadership variables have significant influence on safety performance. Besides, supervisor roles in safety also imposed significant effect to safety performance. Thus, study attempted to determine the direct impact of safety leadership (safety concern, safety policy, and safety motivation) played by the owner-managers on safety performance within the SME manufacturers in Selangor, Malaysia. Furthermore, this study also evaluated the effect of supervisor safety roles in mediating the effect of safety leadership and safety performance. The data was collected among 165 SME manufacturing workers from 37 factories and Partial Least Square Structured Equation Model (PSL-SEM) was performed for data analyses. The results indicated that safety leadership in terms of safety concern, safety policy, and safety motivation has significant impact on safety performance and also supervisor safety roles. However, supervisor safety roles do not mediate the relationship between safety concern, safety policy, and safety motivation and safety performance. Furthermore, safety performance variance is 70% explained by safety leadership variables. This results proved the idea of the importance of direct safety management by the owner-managers in elevating level of OSH among SMEs. This research findings also could serve as initial reference for the involving parties to design and establish safety leadership programmes for SMEs owner-managers. This research concluded that considering the limitations and constrains of the SMEs, safety leadership approach delivered by their the owner-managers could be the best way to improve safety performance constraints.